SPEAKING SKILL IN USING COMMUNITY LANGUAGE LEARNING (CLL) - gunaldi masbirran; andi fauzi (Indonesian Journal of Integrated English Language Teaching, 2017)
The researcher applied Community Language Learning (CLL) in teaching speaking skill. The purpose of this research was to identify the effect of using Community Language Learning (CLL) Method towards speaking skill students who received the class instruction by using CLL than students who do not receive method at the second semester students of ABA Persada Bunda in Pekanbaru. The  design of the research was experimental design with the total number of population are 25 students from the second semester students of ABA Persada Bunda in Pekanbaru. Instrument in this research was an oral test speaking by report. Data were analyzed using t-test. The result of the test showed that the average score of students’ pre test was 68,50 and then the average of students post test was 74,58. The results of this research found that the alternative hypothesis was accepted and rejected a hypothesis null. It can be seen from the t-test (0.000) significant at the level of 0.05. The result of N-Gain of experimental class was 0,31. It meant that the significant of strategy that used in experimental class was Middle because the average of N-Gain was 0.31. From the above explanation, the researcher concluded that Community Language Learning (CLL) Method effective for teaching speaking skill at the second semester students of ABA Persada Bunda in Pekanbaru.